The exploration of using plasma biomarkers of p-tau217 and p-tau181 for screening Alzheimer’s disease in very elderly people - Zhang, Shouzi; Wu, Haiyan; Ma, Li; Li, Rui; Zhang, Li; Liu, Lixin; He, Xuelin; Zhao, Tingyu (Frontiers in Neurology, 2025)
IntroductionBlood-based biomarkers for Alzheimer’s disease (AD), such as phosphorylated tau (p-tau181, p-tau217) and amyloid beta (Aβ), have the potential to serve as screening tools for probable AD in the elderly population.MethodsAD screening [Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA)] was conducted among very elderly individuals residing in a nursing community and a geriatric hospital. Based on cognitive evaluation, participants were categorized into two groups: cognitively normal (n = 62) and probable AD (n = 78). Plasma concentrations of Aβ42, Aβ40, p-tau181, p-tau217, and glial fibrillary acidic protein (GFAP) were measured using the single molecule array (Simoa) platform. Group comparisons of plasma biomarker levels were performed, and receiver operating characteristic (ROC) curve analyses were conducted for each biomarker relative to AD diagnosis.ResultsSignificant differences were observed in plasma p-tau181, p-tau217, and GFAP levels between the cognitively normal and probable AD groups (p < 0.01). In contrast, Aβ42, Aβ40, and the Aβ42/Aβ40 ratio showed no significant differences (p > 0.01). The area under the ROC curve (AUC) was 0.886 for p-tau181, 0.655 for p-tau217, and 0.869 for GFAP.DiscussionPlasma biomarkers p-tau181, p-tau217, and GFAP demonstrate clinical utility in distinguishing AD from normal cognition, suggesting that blood-based testing may serve as a feasible screening tool for early identification of AD in very elderly populations.